Centralized or decentralized—which world will the Internet bring? - Gomery, Douglas (American Enterprise)
One Internet vision of the future involves centralization, bigness, and universal reliance on a small handful of uniform languages, companies, and standards. It predicts that due to Internet use of Sun Microsystems' new Java language, cheap, bare-bones terminals connected to the World Wide Web will replace desktop PCs. However, there are stumbling blocks in the path to this, and they have less to do with technology than with business practices and human psychology, particularly ease of use. It is doubtful that the rise of the Net signals the demise of TV and Hollywood. Rather, in the future, Americans will rely on a multiplicity of media to communicate, entertain, and inform themselves. Nevertheless, the electronic world is unlikely to be as decentralized and open as it has been for the last decade. The info-highway will probably be populated by a small group of large entertainment corporations and several news producers allied with the telecom companies, as well as many new entrants on the fast-expanding information side.